TANGGUNG JAWAB NAZHIR TERHADAP TANAH WAKAF YANG BERALIH FUNGSI MENURUT UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF (STUDI DI KECAMATAN PATUMBAK KABUPATEN DELI SERDANG) - COK SANOFAN HARAHAP (PREMISE LAW JURNAL, 2017)
ABSTRACT Patumbak is a sub-district which has several Wakaf lands in its villages. Nearly all villages have Wakaf lands such as Madrasah (Islamic schools), mosques, foundations, and graveyards for Moslems. In reality, these wakaf lands are not used properly; some of them are still in the form of uncultivated lands and houses for worship which are empty and neglected; therefore, nazhir (sextons) should actively increase these land productivity. The research problems were as follows: how about the legal provisions on the change of function in which it was not in accordance with the wakaf certificate, how anbout the responsibility of nazhir in wakaf land which had changed its function in Patumbak Sub-district, Deli Serdang Regency, and how about the role of BWI (Indonesian Wakaf Agency) in North Sumatera Province in controlling wakaf lands which had been changed their function in Patumbak Sub-district, Deli Serdang Regency. Keywords: Nazhir, Wakaf Land, Change in Function